Genetic Variance of Body Mass Index from Childhood to Early Adulthood - Dellava, Jocilyn E. (2011)
Research has been conducted to determine genetic and environmental components of body mass index (BMI). The portion of phenotypic correlation attributed to genetic, and environmental effects, the effects of puberty stage on BMI means and variances, and consistency of parent/twin report remain largely unknown. The current study seeks to address these questions using four waves of data from 1480 twin pairs in the Swedish Twin Registry: Swedish Twin Study of Child and Adolescent Development. Two Cholesky decomposition models were fit (parental and twin report). For wave 2, a univariate model was fit allowing puberty stage moderation. Parent/twin concordance of reported BMI is high. Genetic factors are largely responsible for phenotypic correlation: puberty stage has a significant effect on BMI variance, with higher genetic variance at more advanced puberty stages. Results provide additional information about this phenotype and suggest early adolescent and parental reports for BMI are roughly equivalent.